2022
DOI: 10.3390/su14042019
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Educators’ Practices in Education for Sustainable Development in China: Evidence from Shandong Province

Abstract: Educators can drive educational change and enable children’s learning for sustainable development. Early childhood education is an important component of Education for Sustainable Development (ESD), and analyzing early childhood educators’ ESD practices can help advance the implementation and realization of ESD. However, the existing overseas studies’ survey instruments do not systematically reflect the basic ideas of ESD. Furthermore, few studies have explored early childhood educators’ ESD practices in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This needs to be done considering that early childhood is the golden age (Almy, 1986 ; Rozi et al, 2022 ), therefore the experience and education they get should not interfere with their brighter future (Bakken et al, 2017 ; Hakim et al, 2020 ). The form of efforts to build the future of early childhood is to provide the best education for them (Cheng & Yu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This needs to be done considering that early childhood is the golden age (Almy, 1986 ; Rozi et al, 2022 ), therefore the experience and education they get should not interfere with their brighter future (Bakken et al, 2017 ; Hakim et al, 2020 ). The form of efforts to build the future of early childhood is to provide the best education for them (Cheng & Yu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…All the world regions and the whole sample present total coverage above 0.92, meaning that the causal paths indicated cover the biggest part of the outcome (the achievement [31], which, according to [21] and [32], validates the existence of robustness). Pre-primary education provides a stimulating environment for children's cognitive, social, and emotional development; it promotes essential skills such as literacy, calculus, and problem-solving [33][34][35][36]. On the other hand, successful completion of lower primary education is crucial for continued education, as it provides a solid foundation for more advanced skills in secondary and higher education [37].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a comparative study found that Japanese and Australian early childhood educators lack well-developed theories and practices in education for sustainability [20]. The findings of another study showed that ESD practices among early childhood educators are usually positive [16]; however, although some early childhood educators claim they are educating the children about sustainable development, they frequently employ rigorous, traditional, direct, and prescriptive interactional methods [2,20]. These previous results might imply that early childhood and kindergarten educators must be given more support to develop a deeper knowledge of sustainability and how to apply it in their contexts and overcome challenges that could prevent them from achieving ESD.…”
Section: Education For Sustainable Development and Kindergarten Teachersmentioning
confidence: 99%
“…Therefore, various initiatives have been taken to establish ESD competency frameworks to solve this issue. To carry out the current investigation, the researcher adopted the framework of [16], who established the "Early Childhood Educators' Education for Sustainable Development Practices Scale" (ECEESDPS) to evaluate the ESD practices of early childhood educators in China. The framework, developed based on United Nations publications and associated research, categorised the core ESD concepts into four categories: values, content, competency, and implementation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation